Changes in Quality of Freeze-Dried Soursop (Annona muricata L.) During High-Temperature Storage with Various Pre-Treatment Methods - Husnun, Fadilah; Suhartatik, Nanik; Kurniawan, Yanuar Aldy; Mustofa, Akhmad (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
Soursop (Annona muricata L.) is a tropical fruit rich in dietary fiber, vitamins, and minerals, including vitamin C, which boosts the immune system and prevents premature aging. Due to its high perishability, further processing such as freeze-drying is necessary to extend its shelf life. This study aimed to determine the changes in quality of freeze-dried soursop during storage at 45°C. A factorial completely randomized design (CRD) was used, with two factors: pre-treatment methods (blanching, blanching with citric acid solution, and blanching with salt solution) and storage duration (0, 2, 4, 6, and 8 weeks). Storage at 45°C for 8 weeks significantly affected the chemical (moisture content, antioxidant activity, total flavonoids, and pH) and physical characteristics (color analysis and physical appearance). The results showed a decrease in moisture content, antioxidant activity, total flavonoids, and brightness level (L), while pH, redness (a*), and yellowness (b*) increased. Keywords: antioxidants, blanching, flavonoids, storage, freeze-dried soursop